THE RELATION BETWEEN THE DEVELOPMENTAL STAGE OF EXPRESSIVE AND RECEPTIVE LANGUAGE AMONG CHILDREN WITH PDD-NOS - CLAUDIA CRIŞAN (Studia Universitatis Babes-Bolyai, 2014)
ABSTRACT. The present study, carried over a period of four years, investigated the existing relation between the developmental stage of receptive and expressive language in the case of two childen with PDD-NOS (Pervasive Developmental Disorder - Not Otherwise Specified). The participants benefited from the intervention based on language and communication stimulation menthol applied in the case of children with Autism Spectrum Disorder (LCSMA - Language and Communication Stimulation Method in Autism; Dascăl Crișan, 2012). According to the results obtained, significant differences were noted between the receptive and expressive language developmental stage, however there were no differences recorded regarding the reptile developmental stage and mental age.